Influenza y embarazo: impacto de la infección y beneficios de la vacuna - Cornejo Cisneros, Enrique (2025)
The influenza virus causes acute respiratory infections seasonally every year and has historically been responsible for pandemics that have resulted in high morbidity and mortality in various periods. Pregnant women and women in the postpartum period constitute an important risk group for complications arising from influenza infection.These complications can occur in the mother (pneumonia, hospitalization), the fetus (congenital anomalies), or represent adverse pregnancy outcomes (fetal death, premature birth, low birth weight). Inactivated influenza vaccines have proven to be an effective and safe tool in preventing influenza-related complications in pregnant women and infants, with their main benefit being the prevention of infections and reduction in hospitalization rates for pregnant women and infants during the first months of life. These benefits are greater when vaccination occurs during the third trimester of pregnancy and appear to be restricted to the first 4 months of the infant's life. It is recommended that pregnant women be vaccinated before the start of the peak influenza season, regardless of the trimester of pregnancy.